2003
DOI: 10.1212/01.wnl.0000078943.50032.fc
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil in vascular dementia

Abstract: Donepezil-treated patients demonstrated significant improvements in cognition and global function compared with placebo-treated patients, and donepezil was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
193
2
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(215 citation statements)
references
References 30 publications
10
193
2
10
Order By: Relevance
“…Six-month treatment with donepezil was shown to significantly improve Clinical Dementia Rating (CDR) scores and activities of daily living in VaD patients (excluding AD and mixed dementia (VaD/AD) patients) [93] . In a later study, donepezil was further demonstrated to significantly improve cognitive function, global function, and activities of daily living versus placebo-treated subjects in a randomized, double-blind, placebo-controlled, 24-week clinical trial comprising 1219 patients with mild to moderate cognitive decline due to probable or possible VaD (according to the NINCDS/AIREN criteria and the Hachinski Ischemia Scale), although adverse effects were reported in the higher-dose group [71,92,94,95] . Moreover, a recent randomized double-blind trial of donepezil in CADASIL showed a significant benefit on executive function and processing speed [46] , although this result was later questioned by Schneider [45] .…”
Section: Donepezilmentioning
confidence: 99%
“…Six-month treatment with donepezil was shown to significantly improve Clinical Dementia Rating (CDR) scores and activities of daily living in VaD patients (excluding AD and mixed dementia (VaD/AD) patients) [93] . In a later study, donepezil was further demonstrated to significantly improve cognitive function, global function, and activities of daily living versus placebo-treated subjects in a randomized, double-blind, placebo-controlled, 24-week clinical trial comprising 1219 patients with mild to moderate cognitive decline due to probable or possible VaD (according to the NINCDS/AIREN criteria and the Hachinski Ischemia Scale), although adverse effects were reported in the higher-dose group [71,92,94,95] . Moreover, a recent randomized double-blind trial of donepezil in CADASIL showed a significant benefit on executive function and processing speed [46] , although this result was later questioned by Schneider [45] .…”
Section: Donepezilmentioning
confidence: 99%
“…There is evidence that treatments approved for cognitive symptoms in patients with Alzheimer's disease may also show symptomatic benefit in patients with vascular cognitive impairment. Although not specifically shown in patients with CAA, trials in patients with vascular dementia indicate that donepezil and galantamine have a modest effect on global cognition reflected by an improvement of 1 to 2 points on the cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAS-cog) (donepezil [131][132][133][134] and galantamine 135,136 ) and improvement on a test for executive functioning. 135 The benefits of memantine and rivastigmine in vascular cognitive impairment are less well established.…”
Section: Treatmentmentioning
confidence: 99%
“…According to the authors, there are insufficient data to support widespread use of these drugs in vascular dementia. The trials meeting the selection criteria for this metaanalysis included three donepezil (307, 308, 319) [31][32][33], two galantamine (GAL-INT-6 and 26) [34,35], one rivastigmine (VantagE) [36], and two memantine trials (MMM300 and 500) [37,38], comprising 3,093 patients on the study drugs and 2,090 patients on placebo (table 1). Cognitive effects on the Alzheimer's Disease Assessment Scale were significant for all drugs, ranging from a mean difference of -1.10 (95% CI -2.15 to -0.05) for rivastigmine to -2.17 for 10 mg daily donepezil (95% CI -2.98 to -1.35).…”
Section: Curative Treatmentmentioning
confidence: 99%